Update on research and clinical translation on specific clinical areas from biology to bedside: Unpacking the mysteries of juvenile idiopathic arthritis pathogenesis. Issue 4 (August 2017) - van Loosdregt, Jorg; van Wijk, Femke; Prakken, Berent; Vastert, Bas
Abstract: In the past decades, we have gained important insights into the mechanisms of disease and therapy underlying chronic inflammation in juvenile idiopathic arthritis (JIA). These insights have resulted in several game-changing therapeutic modalities for many patients. However, additional progress still has to be made with regard to efficacy, cost reduction, minimization of side effects, and dose-tapering and stop strategies of maintenance drugs. Moreover, to really transform the current therapeutic strategies into personalized medicine, we need validated biomarkers to translate increased insights into clinical practice. In this article, we describe recent developments in JIA research and outline how clinical innovations need to go hand in hand with basic discoveries to really effect care for patients. Facilitating the transition from bench to bedside is crucial for addressing the major current challenges in JIA management. When successful, it will set new standards for a safe, targeted, and personalized medicine in JIA.